2019
DOI: 10.1002/gps.5102
|View full text |Cite
|
Sign up to set email alerts
|

Stressful life events and cognitive decline: Sex differences in the Baltimore Epidemiologic Catchment Area Follow‐Up Study

Abstract: Introduction: The reasons why women are at higher risk than men for developing dementia are unclear. Although studies implicate sex differences in the effect of stress on cognitive functioning, whether stressful life events are associated with subsequent cognitive decline has received scant research attention. Methods:In Wave 3 (1993)(1994)(1995)(1996) of the Baltimore Epidemiologic Catchment Area study, 337 men and 572 women (mean age = 47 years) reported recent (within the last year) and remote (from 1981 un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 38 publications
0
5
0
1
Order By: Relevance
“…in child and adolescent years) can have singular repercussions on neurobiological systems that may be implicated in attachment regulation, e.g. the HPA axis (Gerritsen et al, 2010;Kidd, Hamer, & Steptoe, 2013) There is also epidemiological evidence suggesting that middle-aged women with a greater number of recent SLEs demonstrate memory decline over a decade later (Munro et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…in child and adolescent years) can have singular repercussions on neurobiological systems that may be implicated in attachment regulation, e.g. the HPA axis (Gerritsen et al, 2010;Kidd, Hamer, & Steptoe, 2013) There is also epidemiological evidence suggesting that middle-aged women with a greater number of recent SLEs demonstrate memory decline over a decade later (Munro et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It examined the prevalence of psychiatric disorders in the American general population in a sample of 20 000 adults systematically recruited from residential and institutional sources in urban and rural settings, using structured interviews to assess psychiatric disorders according to established diagnostic criteria. The database from this classic study has been utilized for secondary analysis of a vast array of topics in articles published to this very year on many topics, including mood disorders, posttraumatic stress disorder, panic attacks, alcohol and drug dependence, homelessness, antisocial personality disorder, homosexuality, gastrointestinal disease, diabetes, cancer, asthma, stroke, Parkinson's disease, head injury, headaches, sleep disturbance, stress and cognition, obesity, suicidality, social support, healthcare utilization, and mortality (Crum, Storr, Chan, & Ford, 2004; Edwards & Mezuk, 2012; Fleury, Grenier, Bamvita, Perreault, & Caron, 2014; Glass & Bucholz, 2011; Goodwin & Eaton, 2005; Gross, Gallo, & Eaton, 2010; Henriksen, Mather, Mackenzie, Bienvenu, & Sareen, 2014; Krasnova, Eaton, & Samuels, 2019; Kubzansky, Koenen, Jones, & Eaton, 2009; Larson, Owens, Ford, & Eaton, 2001; Lauterbach, Freeman, & Vogel, 2004; Maulik, Eaton, & Bradshaw, 2009; Mezuk, Lohman, Dumenci, & Lapane, 2013; Munro et al, 2019; North, Alpers, Thompson, & Spitznagel, 1996; North, Dinwiddie, Cottler, & Spitznagel, 1991; North, Eyrich, Pollio, & Spitznagel, 2004; North, Kotamarti, & Pollio, 2021; Ramsey, Leoutsakos, Mayer, Eaton, & Lee, 2010; Silver, Kramer, Greenwald, & Weissman, 2001; Woolley, Fredman, Goethe, Lincoln, & Heeren, 2008).…”
Section: The Status Of Older Datamentioning
confidence: 99%
“…Prior research has suggested that older adults may be more likely to experience TEs with increasing age (Creamer & Parslow, 2008) and exhibit greater stress symptoms in response to recent traumas (Kimhi et al, 2012). Cumulative exposure to trauma has also been shown to accelerate age-related declines in physical functioning, cognition, mobility, and self-rated health among older individuals (Blanchette et al, 2019;Krause et al, 2004;Munro et al, 2019) and is related to depressive symptoms and lower life satisfaction among older adults (Ciarleglio et al, 2018;Keinan et al, 2012). However, the bulk of this evidence is from high-income countries.…”
Section: Existing Evidence On Tes and Health In Middleand High-income Settingsmentioning
confidence: 99%